Industrial revolution 4.0 and its impact on the protection of constitutional human rights: a reflection from the Vietnamese context - Nguyen, Thi Thanh Hai (Đại học Quốc gia Hà Nội, 2020)
The fourth industrial revolution has had a profound impact on all areas of social life, including constitutional human rights. In order to promote opportunities and minimize negative impacts of this development process, countries like Vietnam need to ensure that law and policy are adjusted to protect fundamental human rights.